Electronic transport properties of graphene doped by gallium. (14th September 2017) - Mach, J; Procházka, P; Bartošík, M; Nezval, D; Piastek, J; Hulva, J; Švarc, V; Konečný, M; Kormoš, L; Šikola, T
Abstract: In this work we present the effect of low dose gallium (Ga) deposition (<4 ML) performed in UHV (10 −7 Pa) on the electronic doping and charge carrier scattering in graphene grown by chemical vapor deposition. In situ graphene transport measurements performed with a graphene field-effect transistor structure show that at low Ga coverages a graphene layer tends to be strongly n-doped with an efficiency of 0.64 electrons per one Ga atom, while the further deposition and Ga cluster formation results in removing electrons from graphene (less n-doping). The experimental results are supported by the density functional theory calculations and explained as a consequence of distinct interaction between graphene and Ga atoms in case of individual atoms, layers, or clusters.